Garlic and Watermelons - Kickey, Cameron; Feeny, Lauren (United States, 2005)
Summer 2003. With the Athens 2004 Summer Olympics just over a year away, forty Gypsy families are forced to abandon their settlement next to the main Olympic stadium, so that the land can be used for a parking lot.The film follows Prokopis Nikolaou,a produce vendor who lived his entire life in this settlement, as he struggles to find a new home for himself and his family.The local mayor agreed to pay the Roma rent subsidies in exchange for vacating the land, but the money proves elusive and the families are forced to move from place to place due to evictions and sub-standard living conditions. Feeling angry and fooled, Prokopis becomes an unofficial spokesman for the forty families, fighting for both their dignity and the money they were promised. He meets with human rights activists, takes his battle with the mayor to the courts, and shares his story with the international media that descend on Athens in the weeks leading up to the Olympic Games.
Verzio Film Festival Submission ; Coproduction: USA, Greece
Verzio Film Festival Submission
Keywords: Documentary films